Safety in the domestic kitchen - Walker, William (Australia: Video Education Australasia, 2022)
With the aid of fun characters, Conrad and Candy, the program covers clothing, avoiding cuts, treating cuts, burns and scalds, lifting, and other golden rules for kitchen safety and hygiene.